THE RELATIONSHIP OF KNOWLEDGE AND ATTITUDE TO OCCUPATIONAL HEALTH AND SAFETY BEHAVIOR IN MACHINING WORKSHOP - Dewangga, Andrian Wisnu; Djatmiko, Riswan Dwi; Majid, Aulia (Jurnal Dinamika Vokasional Teknik Mesin, 2025)
This research aims to determine the relationship between knowledge and attitudes towards Occupational Health and Safety (OHS) behavior in the Vocational School workshop. This research is descriptive research with a quantitative approach. The research population was Machining Engineering students and the sample was determined using purposive sampling technique. The data collection technique uses a closed questionnaire. Data were processed using descriptive analysis techniques and regression analysis. The results of the research show that (1) there is a significant relationship between knowledge and OHS behavior of class which is significant, OHS knowledge and attitudes together towards the OHS behavior of class X students majoring in Mechanical Engineering at Vocational School. This conclusion provides factors influencing students' OHS behavior. The implications of this research are providing OHS knowledge to improve student behavior in OHS.